PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS VIII SMPN 15 PADANG - NINDA PRATIWI (Departemen Matematika, 2018)
The ability of mathematical reasoning is one of the abilities in mathematics learning that must be possessed by every students. However, the 8thgrade of mathematics in Junior High School number 15 Padang, student’s mathematical reasoning abilityis not optimal. Generative learning is one of learning model that can improve the ability of mathematical reasoning. The aims of this research are to describe the development of student’s mathematical reasoning abilities using generative learning model and to describe the differences in the ability of student's mathematical reasoning usinggenerative learning model with the ability of student's mathematical reasoning usingdirect learning model. The types of research are descriptive and quasi-experimental with Randomized Control-Group Only Design. The results showed that theability of student’s mathematical reasoning which was taught by using generative learning model had increased. Furthermore, based on the hypothesis test result, it was found that the ability of student's mathematical reasoning which was taught by usinggenerative learning model are better than the ability of student's mathematical reasoning which was taught by direct learning model. So, it can be concluded that there is influences ofgenerative learning model for the ability of mathematical reasoning.Keywords - Generative Learning Model, The Ability of Mathematical Reasoning.